MACHINE TO MACHINE (M2M) CONNECTIVITY BUSINESS FEASIBILITY ANALYSIS AND STRATEGY DEVELOPMENT CASE STUDY OF PT XYZ, A COMPANY IN INDONESIA, WITH SWOT ANALYSIS - Safrian Andromeda; Bahar Amal; Ni Luh Bella Dwijaksara (Yayasan Nusantara Hasana Berdikari, 2024)
From 2016 to 2018, the number of new Very Small Aperture Terminal (VSAT) customers at PT XYZ declined. According to Safrian (2018), VSAT is included in quadrant two of the (Strength, Weakness, Opportunity, and Threat) SWOT diagram, so it requires diversification to create new opportunities and increase revenue. This research was conducted to analyze the feasibility of using M2M as a form of diversification. M2M was compared with VSAT using the Return on Investment (ROI) method and performance testing. Alternative M2M business strategies are also using the SWOT analysis. From the ROI results, M2M had 74%. M2M connectivity can provide more benefits with more efficient investment. From the performance test, M2M latency of 33ms is in the outstanding category, while VSAT of 596ms is in the poor category. The SWOT analysis found that the company entered quadrant one, with the strategy chosen being the SO strategy, which focuses on developing M2M technology.